Analisis Minat Mahasiswa Memilih Program Studi PIAUD Pada Perguruan Tinggi Keagamaan Islam Negeri Aceh - Elfiadi, Elfiadi; Sari, Mutia (Universitas Islam Negeri Jurai Siwo Lampung, 2024)
This study aims to analyze student’s interest in choosing the Early Childhood Islamic Education (PIAUD) study program at State Islamic Religious Higher Education Institutions (PTKIN) in Aceh. Utilizing a qualitative survey method, this research explores the factors influencing students' choicesi regarding the PIAUD program. The findings reveal that student interest is shaped by a combination of internal and external motivations. A total of 51.9% of students chose the PIAUD program due to personal interest, 26% due to parental influence, and 18% due to favorable career prospects. The primary source of information was the family, followed by social media, indicating the strong role of the family in students' academic decisions.-making. Social factors such as peers and teachers, also played a role in shaping students’ interest. Although many students ware initially influenced by external factors, the findings suggest that their internal motivation and interest developed over time through the educational process. These results highlight the importance of family support, social environment, and career prospects in influcing students’ interest in the PIAUD program, which can serve as a foundation for developing promotional strategies and enhancing the quality of the study program in the future.